Synthesis, Characterization, and Structural Studies of Some Homo- and Heteroleptic Cu(I) Complexes Bearing 6,6′-Bis(phenylethynyl)-2,2′-Bipyridine Ligand - Rayya A. Al-Balushi; Md. Serajul Haque Faizi; Md. Mushtaque; Idris J. Al-Busaidi; Muhammad S. Khan (Inorganics)
Coordination-driven Cu(I) complexes constitute an interesting class of materials with rich opto-electronic properties and diverse applications. Various homo- and heteroleptic Cu(I) complexes have been reported in the literature. In continuation with our quest for new materials, we report herein two novel coordination-driven self-assembled Cu(I) complexes: the homoleptic (1) and the heteroleptic (2) complexes based on the 6,6′-bis(phenylethynyl)-2,2′-bipyridine (L1) and 2,9-dimethyl-1,10-phenanthroline (dmph) ligands. L1 was prepared by a Pd(II)-catalyzed Sonogashira cross-coupling reaction between phenylactylene and 6,6′-dibromo-2,2′-bipyridine. Homo- and heteroleptic Cu(I) complexes were obtained by the self-assembly of L1 and dmph ligands. Complexes (1) and (2) were obtained in high yields, and are soluble in common organic solvents and stable at room temperature over a long period of time. The optical (absorption and emission) properties of both complexes were evaluated. The optical properties in solution are a function of the ligands and varied for the complexes. Complex (2) was also characterized by single-crystal X-ray diffraction and the intermolecular interaction was studied using Hirschfeld surface analysis. In the solid state, complex (2) exhibited four-coordinate distorted tetrahedral geometry around Cu(I). Density functional theory (B3LYP/6-311++G(d,p) was utilised to determine various molecular descriptors.